Combinatorial sputtering and degradation behaviour of photoluminescence Europium Titanium Oxide thin films - Chen, Junfeng (Cranfield University, 2024)
The most common type of solar cell is the crystalline silicon (c-Si) cell, which has a low cost of production and a high efficiency of energy conversion and is widely used in various applications that require solar power. Inefficiencies associated with PV devices mainly stem from energy conversation mismatches between solar radiation and the PV spectral response. Photoluminescent (PL) thin films possess the capability to absorb and re-emit specific photons, thereby minimising energy losses within the PV system. In this thesis, PL thin films have been fabricated using the physical vapour deposition (PVD) method, synthesised Europium oxide and Titanium oxide coating. A range of Europium Titanium Oxide (ETO) luminescence thin films, with concentrations varying from 0 at% to 100 at% in Eu/(Eu+Ti), were fabricated using combinatorial sputtering. The samples underwent heat treatment annealing at 450˚C and 600˚C, resulting in changes to the phase, structure, and optical properties. The effect of composition and annealing temperature on the characterisations of the ETO thin film samples were comprehensively studied using SEM, EDX, XRD, UV–Vis spectrophotometer, Raman spectrometer, fluorescence spectrometer, and solar simulator. Transmittance and bandgap variations are observed and influenced by annealing temperature and europium ratios. The bandgap energy variation is identified as a crucial factor affecting photon absorption and the luminescent properties of the films. Fluorescence spectroscopy was used to examine the photoluminescence properties of the thin films. Excitation peaks at 394 nm ( 7F0'→5L6') and 464 nm (7F0→ 5D2) are identified as the most intense in excitation spectra, while in emission spectra the strongest emission intensity peak at 613 nm (5D0→7F2) exhibits a higher branching ratio in fluorescence spectra. Furthermore, an investigation into the optical and fluorescence properties of luminescence thin films comprising Eu(dbm)3 and CuInS2/ZnS in conjunction with PMMA and PVA matrices has been conducted. The characteristics of these films were analysed both before and after degradation testing, with a comparative assessment made against ETO thin films. In addition, an intriguing correlation between bandgap values and power conversion efficiency is established. Films with narrower bandgaps demonstrate reduced power conversion efficiency due to increased photon absorption, scattering and escape from the substrate edge. These findings contribute valuable insights into tailoring the properties of luminescence thin films for potential applications, particularly in the realm of optoelectronic devices.
Rao, Jeff - Associate Supervisor
Keywords: lanthanide materials; down-conversion; combinatorial sputtering; fluorescence; degradation